Brain-Specific SNAP-25 Deletion Leads to Elevated Extracellular Glutamate Level and Schizophrenia-Like Behavior in Mice - Hua Yang; Mengjie Zhang; Jiahao Shi; Yunhe Zhou; Zhipeng Wan; Yicheng Wang; Yinghan Wan; Jun Li; Zhugang Wang; Jian Fei (Neural Plasticity)
Several studies have associated reduced expression of synaptosomal-associated protein of 25 kDa (SNAP-25) with schizophrenia, yet little is known about its role in the illness. In this paper, a forebrain glutamatergic neuron-specific SNAP-25 knockout mouse model was constructed and studied to explore the possible pathogenetic role of SNAP-25 in schizophrenia. We showed that SNAP-25 conditional knockout (cKO) mice exhibited typical schizophrenia-like phenotype. A significantly elevated extracellular glutamate level was detected in the cerebral cortex of the mouse model. Compared with Ctrls, SNAP-25 was dramatically reduced by about 60% both in cytoplasm and in membrane fractions of cerebral cortex of cKOs, while the other two core members of SNARE complex: Syntaxin-1 (increased ~80%) and Vamp2 (increased ~96%) were significantly increased in cell membrane part. Riluzole, a glutamate release inhibitor, significantly attenuated the locomotor hyperactivity deficits in cKO mice. Our findings provide in vivo functional evidence showing a critical role of SNAP-25 dysfunction on synaptic transmission, which contributes to the developmental of schizophrenia. It is suggested that a SNAP-25 cKO mouse, a valuable model for schizophrenia, could address questions regarding presynaptic alterations that contribute to the etiopathophysiology of SZ and help to consummate the pre- and postsynaptic glutamatergic pathogenesis of the illness.